The consumers of the digital age: Which place for the right to information? - AZEVEDO AMORIM, Ana Clara (Revista Jurídica Portucalense, 2023)
Consumers’ protection is traditionally based on the information asymmetry by comparison with the professionals. However, the transition to the information society led to a paradigm change in marketplace relationships. With emphasis on the advertising legal framework, this study addresses the factors which determine the consumers’ economic decisions in the digital age, aiming to show whether there are still grounds for the established information duties.